Analisis Tingkat Kerukunan Antar Umat Beragama di Universitas Negeri Medan - Mangido Nainggolan; Reza Artha Mevia Lumban Gaol; Novi Kristina Sinabutar; Bryan Hizkia; Dear Chio Sembiring; Widya Purnama Sitanggang; Maria Anatasyia Br. Siregar; Nella Juriska RajaGukguk; Yefta Darniati Sinaga (Departement of Mathematics Education, 2024)
This research aims to analyze the level of inter-religious harmony at the State University of Medan (UNIMED) and identify the factors that influence it. Using a qualitative approach, data is collected through in-depth interviews, participant observation, and document study involving students from various religious backgrounds at UNIMED. The data is thematically analyzed to identify patterns, categories, and main themes related to inter-religious harmony as well as the supporting and inhibiting factors. The research findings are expected to provide useful information and recommendations for UNIMED and other educational institutions in promoting harmony and tolerance among the academic community.